Chrześcijańskie sacrum? - Adamczyk, Dariusz; Bębas, Sylwester (Collectanea Theologica, 2019)
In this paper the authors characterise the Christian notion of the sacred. They emphasise that the sacred is a term referring to an unspecified Mystery, that reference to the sacred sphere is associated with religion, and that the concept of the sacred is the central religious category. This gives ultimate meaning to human existence. All players get their sacredness from God. To the realm of the sacred belong also holy places. The article ends with a summary in which the authors point out that the Christian concept of the sanctity is very rich in contents.